Peter Nicholas Tarling: A Tribute - Ooi , Keat Gin (Penerbit Universiti Sains Malaysia (USM Press), 2017)
Nicholas Tarling is one of the foremost historians of the role of the British in Southeast Asia during the nineteenth and twentieth centuries. Well established in his feld of expertise specifcally focusing on British policy in and towards Malaya / Malaysia, Indonesia, Siam / Thailand and Myanmar (Burma), he has authored and edited close to 40 books including the two volume The Cambridge History of Southeast Asia (Cambridge, 1992), and more than 90 scholarly journal articles in an academic career spanning more than half a century. Nick, as he is aﬀectionately known, is the quintessential scholar: a consummate researcher and a prolifc writer. Poring through literally miles of archival documents is but second nature to him; likewise putting pen to paper for his fndings, analysis, interpretations, thoughts and opinions to churn out manuscript after manuscript for publication. Apart from history, his forte, Nick wrote on higher education and on the performing arts (music and theatre).